2015
DOI: 10.1371/journal.pntd.0004226
|View full text |Cite
|
Sign up to set email alerts
|

Deltamethrin Resistance Mechanisms in Aedes aegypti Populations from Three French Overseas Territories Worldwide

Abstract: Background Aedes aegypti is a cosmopolite mosquito, vector of arboviruses. The worldwide studies of its insecticide resistance have demonstrated a strong loss of susceptibility to pyrethroids, the major class of insecticide used for vector control. French overseas territories such as French Guiana (South America), Guadeloupe islands (Lesser Antilles) as well as New Caledonia (Pacific Ocean), have encountered such resistance.Methodology/Principal FindingsWe initiated a research program on the pyrethroid resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
103
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(115 citation statements)
references
References 46 publications
8
103
2
2
Order By: Relevance
“…In this study, we find that the miR-932-mimic-injected mosquitoes become more resistant to deltamethrin, while the miR-932-inhibitor-injected mosquitoes become more susceptible to deltamethrin, suggesting that miR-932 participates in the regulation of pyrethroid resistance. The role of miR-932 in pyrethroid resistance also offers new ideas about exploring the mechanisms of insecticide resistance, which would help to make more pertinent measures in controlling mosquito populations (Dusfour et al 2015). All the way through, there are two main molecular mechanisms that can elucidate insecticide resistance, one is target site modification represented by knock-down effect, another is metabolic detoxification, such as the cytochrome P450 monooxygenases (Itokawa et al 2015, Vera-Maloof et al 2015.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we find that the miR-932-mimic-injected mosquitoes become more resistant to deltamethrin, while the miR-932-inhibitor-injected mosquitoes become more susceptible to deltamethrin, suggesting that miR-932 participates in the regulation of pyrethroid resistance. The role of miR-932 in pyrethroid resistance also offers new ideas about exploring the mechanisms of insecticide resistance, which would help to make more pertinent measures in controlling mosquito populations (Dusfour et al 2015). All the way through, there are two main molecular mechanisms that can elucidate insecticide resistance, one is target site modification represented by knock-down effect, another is metabolic detoxification, such as the cytochrome P450 monooxygenases (Itokawa et al 2015, Vera-Maloof et al 2015.…”
Section: Discussionmentioning
confidence: 99%
“…However, the V1016G mutation has not been reported in Latin America [31,32,46,47]. Instead, mutation V1016I was found, and often coexists with F1534C in South and North America, such as Venezuela [48], three French overseas territories [49], Brazil [50,51,52], Mexico [53], and the USA [54]. More recently, V1016I and F1534C were detected in Ghana, Africa [55], and a new mutation, T1520I, was found along with the F1534C mutation in a population in India [56].…”
Section: Identification Of Single Nucleotide Polymorphisms (Snps)mentioning
confidence: 99%
“…So far, V1016G has been detected only in Southeast Asia [34,37,40,41,44,45], whereas V1016I is distributed in South and North America [48,49,50,51,52,53]. More recently, V1016G, along with F1534C, was also detected in Ghana.…”
Section: Evolution Of Kdr Mutations In Aedes Aegyptimentioning
confidence: 99%
“…aegypti and Ae. albopictus showed that most of detoxification enzymes linked to insecticide resistance belong to the cytochrome P450 genes [23, 24]. Target insensitivity is due to mutations that reduce the binding affinity between the insecticide and its physiological target.…”
Section: Introductionmentioning
confidence: 99%
“…In many mosquito species, including Ae. aegypti , kdr related to pyrethroids and DDT has been located in segment 6 of domain II [23, 2931], with other mutations at the same position ( I1011M , I1011V , V1016G and V1016I ) [32]. In South-East Asia, for example, two major voltage-gated sodium channel haplotypes ( S989P  +  V1016G and F1534C ) confer resistance of Ae.…”
Section: Introductionmentioning
confidence: 99%